KEBIJAKAN SISTEM PEMELIHARAAN MESIN PADA PABRIK KOPI SARIWANGI BUMI MUTIARA - Santi, Santi (Fakultas Ekonomi Universitas Tadulako, 2017)
This study aims to determine and analyze the engine maintenance performed Sariwangi Earth Pearl Factory Shop and to find out whether the policies implemented have been streamlined. To achieve these objectives, using quantitative methods and mathematical statistics as a tool to help decide the maintenance policies to be taken at a certain time.The results showed that the annual preventive maintenance Rp. 4.200.000, -, while corrective annual fee of Rp. 4.500.000, -. Coffee Factory Sariwangi then implement preventive maintenance can save maintenance cost Rp. 300.000, -.